The Physical and Chemical Properties of Marshmallow made from Bufallo (Bubalus bubalis) Hide Gelatin Compared to Commercial Gelatin - Umar Santoso; Yudi Pranoto; Yessy Tania Afriyanti; Sri Mulyani (Journal of Applied Food Technology, 2019)
In recent years, there is increasing demand of gelatin application, particularly in confectionary products such as marshmallow. Due to halal issue of predominant porcine gelatin, alternative gelatin from other source, like buffalo hide, is critically needed. This study aimed to analyze physical and chemical properties of marshmallow made from buffalo hide gelatin, which was compared to commercial marshmallow and those made using commercial gelatin. Conducted in two stages, the first part was gelatin extraction from buffalo hide and its quality analyses. The second was marshmallow preparation from the gelatin and its analyses. Concentration of buffalo hide gelatin was 4%, 5%, dan 6%, whereas commercial gelatin was 7%, 8%, and 9%. The experiment was repeated three times and all determination were performed in duplicated. Results showed that marshmallow from buffalo hide gelatin contained 15,5 – 18,40 % (wb) moisture; 0,64 - 1.16% (db) ash content; 43,34 – 48,83 % (db) total sugar; and 24,25 – 28,73 % (db) reducing sugar. Textural analyses indicated that the highest value of marshmallow hardness (129.50 g/mm2) and highest value of springiness (5.70 mJ/mm2) were obtained by marshmallow made using 5% and 6% buffalo hide gelatin, respectively), thus concluded that buffalo hide is potential halal gelatin source to produce marshmallow